Evaluation of PTEN, PI3K, MTOR, and KRAS expression and their clinical and prognostic relevance to differentiated thyroid carcinoma - Duman, Berna B.; Kara, Oğuz I.; Uğuz, Aysum; Ates, Berna T. (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Important signalling pathways play fundamental roles in the pathogenesis of thyroid carci- noma (TC). PTEN, mTOR, PI3K-p85 and K-Ras are the principal factors involved in these signalling pathways. To immunohistochemically examine the expressions of PI3K, mTOR and PTEN in patients suffering from follicular TC, papillary TC or variants thereof, as well as to investigate KRAS mutations via PCR to determine their clinical and prognostic relevance to differentiated thyroid cancer. Material and methods: The expression of PTEN, PI3K-p85 and mTOR was immunohistochemically examined, and the mutation of K-Ras was examined via PCR. The results obtained were compared to the clinico-pathologic characteristics of the patients. Results: A significant correlation was found between p85 expression and lymphovascular invasions and between PTEN expression and multifocality (p = 0.048 and p = 0.04, respectively), and a correlation between p85 and capsular invasion was found, with a borderline statistical significance (p = 0.056). No expression of PTEN, p85 or Mtor was detected in normal tissue. K-Ras mutation was examined in 66 of the 101 patients (57.4%), and the percentage of patients exhibiting a K-Ras mutation was 17.4%. All of the patients exhibiting a K-Ras mutation were women (p = 0.047). The disease-free survival was 44.6 months (95% CI: 37.9–51.3) and was statistically significantly higher in the group that displayed level 1 or lower expression of p85 (p = 0.043). Conclusions : The expression levels of the aforementioned markers were significantly higher in TC cells than in normal tissue. A significant correlation was detected between K-Ras mutation and gender. This study demonstrates that p85 and PTEN are markers that should be evaluated in further studies of TC.